Systematic surgical approach to juvenile angiofibroma - Raluca Oana Pulpă; Viorel Zainea; Cătălina Voiosu; Ruxandra Oana Aliuș; Andreea Rusescu; Irina-Gabriela Ioniță; Veronica Epure; Dragoș Octavian Palade; Răzvan Hainăroșie (Journal of Mind and Medical Sciences)
Introduction. Juvenile nasopharyngeal angiofibroma is a rare type of benign vascular tumour that affects only young males, especially those between the ages of 9 and 19. Therapeutic management depends on the extent of the lesion, being conditioned by the complexity of the anatomy of the skull base and the risk of massive bleeding due to the abundant vascular supply. The purpose of this article is to describe the modern approach to juvenile nasopharyngeal angiofibroma, starting from the general knowledge on this topic and presenting the experience of our clinic. Materials and Methods. A retrospective study was conducted on 10 male patients with juvenile angiofibroma, with clinical and imaging diagnoses, confirmed by post-ablative histopathological examination. From the 10 juvenile angiofibroma case treated in our clinic, 4 of them were less extensive, 2 with invasion to the pterygopalatine fossa, 3 involving the infratemporal fossa and 1 with minimal intracranial extension. Results. Combined approach (endoscopic trans-nasal approach and Caldwell Luc approach) was necessary in the treatment of a IIC case. Follow-up after surgery was done using MRI scans every 6 months. Recurrence was encountered in one case (9 months from the first surgery), and needed reintervention to remove the residual tumour. Conclusions. Even if it is a rare condition, the development of specific materials and techniques (endoscopic, embolization) has been considerable, allowing the reduction of intraoperative bleeding and residual tumour tissue, in conditions of minimal interference with the facial anatomy of such young patients.